Uniqueness of Limit Cycles for a Class of Cubic Systems with Two Invariant Straight Lines - Xiangdong Xie; Fengde Chen; Qingyi Zhan (Discrete Dynamics in Nature and Society)
A class of cubic systems with two invariant straight lines dx/dt=y(1-x2),  dy/dt=-x+δy+nx2+mxy+ly2+bxy2. is studied. It is obtained that the focal quantities of O(0,0) are, W0=δ; if W0=0, then W1=m(n+l); if W0=W1=0, then W2=−nm(b+1); if W0=W1=W2=0, then O is a center, and it has been proved that the above mentioned cubic system has at most one limit cycle surrounding weak focal O(0,0). This paper also aims to solve the remaining issues in the work of Zheng and Xie (2009).